Sutan Puasa founder of Kuala Lumpur - Lubis, Abdur-Razzaq (Areca Books, 2018)
Who was the founder of Kuala Lumpur, the capital city of Malaysia? Textbook history credits the Bugis chief of Klang, Raja Abdullah, while the Chinese regard the third Kapitan China, Yap Ah Loy, as the legendary founder. But closer examination reveals that the founding myths of Kuala Lumpur have omitted the earliest chapter of the city's history.